Globalization and Education (Journal of Education and Educational Development, 2020)
The concept of globalization has been introduced due to technical advancements that has made the world a global village. The world as is now has never been before; it is now a world where multicultural societies have developed, trade and transactions are made between countries, technology reaches every part of the world, and internet has connected every possible idea, opinion, person, and commodity with the rest of the world. In this world of globalization, education has taken a central role, as without education globalization cannot be germinated. Education is a national issue and as such, each country has its own educational policies that are emblems of that country’s cultural values, belief system and historical realities. Nevertheless, the globalized world demands for multiculturalism, and commonalities amongst communities to be promoted so as to bring the world closer to accepting cultural diversities and celebrating commonalities. For these aims, educational institutions become institutions for promoting globalization by introducing various cultural and traditional beliefs to the new generation. Recently, globalization has become a popular subject of debate in national and international circiles. Globalization links individuals and institutions across the world through economic forces, digital technologies, and communication. It is moreover subjected to higher living standards, international affiliations, and multiple types of freedom. However, a major part of the world consists of under developed countries where technological advancements, communication, trade and commerce along with other economic activities are not enough to support them to be a part of the global society.